2016
DOI: 10.1002/2016gl067730
|View full text |Cite
|
Sign up to set email alerts
|

Surface temperature dependence of tropical cyclone‐permitting simulations in a spherical model with uniform thermal forcing

Abstract: Tropical cyclone (TC)‐permitting general circulation model simulations are performed with spherical geometry and uniform thermal forcing, including uniform sea surface temperature (SST) and insolation. The dependence of the TC number and TC intensity on SST is examined in a series of simulations with varied SST. The results are compared to corresponding simulations with doubly periodic f‐plane geometry, rotating radiative convective equilibrium. The turbulent equilibria in simulations with spherical geometry h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 22 publications
8
48
0
Order By: Relevance
“…Though other factors like surface relative humidity also affect the air‐sea disequilibrium, an increase with SST is the leading‐order behavior for radiatively forced climate changes and this, in turn, increases potential intensity [ Emanuel , ; Emanuel and Sobel , ]. In contrast, the influence of SST on TC genesis is still unclear, particularly at the basin scale [ Bengtsson et al , ; Emanuel et al , ; Sugi et al , ; Zhao et al , ; Knutson et al , ; Held and Zhao , ; Emanuel , ; Merlis et al , ; Zhao et al , ; Merlis et al , ; Knutson et al , ; Sugi et al , ; Walsh et al , ]. We emphasize that our analysis of SST G is a frequency‐independent statistic, and neither implies that a warmed SST environment favors nor disfavors TC genesis frequency.…”
Section: Warming Trends In Sst At Tc Genesismentioning
confidence: 99%
“…Though other factors like surface relative humidity also affect the air‐sea disequilibrium, an increase with SST is the leading‐order behavior for radiatively forced climate changes and this, in turn, increases potential intensity [ Emanuel , ; Emanuel and Sobel , ]. In contrast, the influence of SST on TC genesis is still unclear, particularly at the basin scale [ Bengtsson et al , ; Emanuel et al , ; Sugi et al , ; Zhao et al , ; Knutson et al , ; Held and Zhao , ; Emanuel , ; Merlis et al , ; Zhao et al , ; Merlis et al , ; Knutson et al , ; Sugi et al , ; Walsh et al , ]. We emphasize that our analysis of SST G is a frequency‐independent statistic, and neither implies that a warmed SST environment favors nor disfavors TC genesis frequency.…”
Section: Warming Trends In Sst At Tc Genesismentioning
confidence: 99%
“…TCs are among the most dangerous manifestations of organized convection, with several impacts including wind damage, storm surge, and potentially extreme rainfall. Studies of rotating RCE have shown that self‐aggregation can take the form of spontaneous tropical cyclogenesis (Bretherton et al, ; Boos et al, ; Davis, ; Held & Zhao, ; Khairoutdinov & Emanuel, ; Merlis et al, ; Muller & Romps, ; Nolan et al, ; Reed & Chavas, ; Shi & Bretherton, ; Wang et al, ; Wing et al, ; Zhou et al, , ). Idealized simulations in these studies led to TC formation from both a prescribed moist bubble or vortex and white noise random convection.…”
Section: Introductionmentioning
confidence: 99%
“…These projections are obtained using high-resolution global climate models [e.g., Murakami et al, 2012;Zhao and Held, 2012], high-resolution idealized experiments [Rappin et al, 2010;Merlis et al, 2016], as well as using dynamical downscaling using regional climate models [Knutson et al, 2008;Bender et al, 2010]. For instance, Knutson et al [2015] considered storms produced by a global model, but then used a higher-resolution model in order to simulate the most intense storms.…”
Section: Introductionmentioning
confidence: 99%